An impact of age on respiratory syncytial virus infection in air-liquid-interface culture bronchial epithelium - Ito, Kazuhiro; Daly, Leah; Coates, Matthew (Frontiers in Medicine, 2023)
Background: Elderly people are known to be vulnerable to virus infection. However, this has not been appropriately tested in in vitro studies due to a lack of appropriate virus infection models. In this report, we investigated the impact of age on respiratory syncytial virus (RSV) in pseudostratified air-liquid-interface (ALI) culture bronchial epithelium, which more closely mimic human airway epithelium morphologically and physiologically, than submerged cancer cell line cultures. Methods: RSV A2 was inoculated apically to the bronchial epithelium obtained from 8 donors with different ages (28-72 years old), and time-profiles of viral load and inflammatory cytokines were analyzed. Results: RSV A2 replicated well in ALI-culture bronchial epithelium. The viral peak day and peak viral load were similar between donors at ≤60 years old (n=4) and >65 years old (n=4) (elderly group), but virus clearance was impaired in the elderly group. Furthermore, area under the curve (AUC) analysis, calculated from viral load peak to the end of sample collection (from Day 3 to 10 post inoculation), revealed statistically higher live viral load (PFU assay) and viral genome copies (PCR assay) in the elderly group, and a positive correlation between viral load and age was observed. In addition, the AUCs of RANTES, LDH and dsDNA (cell damage marker) were statistically higher in the elderly group, and the elderly group showed a trend of higher AUC of IL-8, CXCL10 and mucin production. The gene expression of p21CDKN1A (cellular senescence marker) at baseline was also higher in the elderly group, and there was a good positive correlation between basal p21 expression and viral load or RANTES (AUC). Conclusion: Age was found to be a key factor affecting viral kinetics and biomarkers post virus infection in an ALI-culture model. Currently, novel or innovative in vitro cell models are introduced for virus research, but when virus studies are conducted, similarly to working with other clinical samples, the age balance are important to obtain more accurate results.